Accelerated antibody discovery targeting the SARS-CoV-2 spike protein for COVID-19 therapeutic potential. (28th August 2021) - Mullen, Tracey E; Abdullah, Rashed; Boucher, Jacqueline; Brousseau, Anna Susi; Dasuri, Narayan K; Ditto, Noah T; Doucette, Andrew M; Emery, Chloe; Gabriel, Justin; Greamo, Brendan; Patil, Ketan S; Rothenberger, Kelly; et al.
Abstract: Background: Rapid deployment of technologies capable of high-throughput and high-resolution screening is imperative for timely response to viral outbreaks. Risk mitigation in the form of leveraging multiple advanced technologies further increases the likelihood of identifying efficacious treatments in aggressive timelines. Methods: In this study, we describe two parallel, yet distinct, in vivo approaches for accelerated discovery of antibodies targeting the severe acute respiratory syndrome coronavirus-2 spike protein. Working with human transgenic Alloy-GK mice, we detail a single B-cell discovery workflow to directly interrogate antibodies secreted from plasma cells for binding specificity and ACE2 receptor blocking activity. Additionally, we describe a concurrent accelerated hybridoma-based workflow utilizing a DiversimAb™ mouse model for increased diversity. Results: The panel of antibodies isolated from both workflows revealed binding to distinct epitopes with both blocking and non-blocking profiles. Sequence analysis of the resulting lead candidates uncovered additional diversity with the opportunity for straightforward engineering and affinity maturation. Conclusions: By combining in vivo models with advanced integration of screening and selection platforms, lead antibody candidates can be sequenced and fully characterized within one to three months.